2019
DOI: 10.1111/jcmm.14265
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of carbonic anhydrase I enhances the malignant potential of exosomes secreted by prostatic tumour cells

Abstract: We report results showing that the silencing of carbonic anhydrase I (siCA1) in prostatic (PC3) tumour cells has a significant impact on exosome formation. An increased diameter, concentration and diversity of the produced exosomes were noticed as a consequence of this knock‐down. The protein composition of the exosomes' cargo was also altered. Liquid chromatography and mass spectrometry analyses identified 42 proteins significantly altered in PC3 siCA1 exosomes compared with controls. The affected proteins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Passive exosome formation involves the participation of lipids (ceramide), tetraspanins (CD63), and heat shock proteins independently of ESCRT [ 59 , 60 , 61 ]. Studies have shown localization of lipid metabolizing enzyme sphingomyelinase (SMase) and phospholipase D2 (PLD2) to MVB membrane induces the inward curvature required for exosome formation [ 62 , 63 , 64 ].…”
Section: Biogenesismentioning
confidence: 99%
“…Passive exosome formation involves the participation of lipids (ceramide), tetraspanins (CD63), and heat shock proteins independently of ESCRT [ 59 , 60 , 61 ]. Studies have shown localization of lipid metabolizing enzyme sphingomyelinase (SMase) and phospholipase D2 (PLD2) to MVB membrane induces the inward curvature required for exosome formation [ 62 , 63 , 64 ].…”
Section: Biogenesismentioning
confidence: 99%
“…Carbonic anhydrases have 14 different isoforms, and the distribution patterns of the isoenzymes differ [ 28 ]. Silencing carbonic anhydrase I enhances the malignant potential of exosomes secreted by prostate tumour cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have pointed to the importance of the CAs and their inhibitors as an indicator for various diseases (Finkelmeier et al, 2018; Koutnik et al, 2017; Li et al, 2019; Mehta et al, 2018; Zamanova et al, 2019). Of particular importance is the human isozyme CA1, which has been identified as a potential marker of various cancers (breast, oral, colorectal, lung, prostate), ankylosing spondylitis, diabetes, Sjogren's syndrome and pancreatitis (Bánová Vulić et al, 2019; Chang et al, 2010, 2012; Frulloni et al, 2000; Giusti et al, 2007; Hu et al, 2007; Inagaki et al, 1991; Kardoush et al, 2017; Lee et al, 2015; Liu et al, 2012; Peng et al, 2012; Ryu et al, 2006; Torella et al, 2014; Wang et al, 2016; Zheng et al, 2015). Also encouraging for early detection, the level of CA1 can be determined at point of care (POC) by its presence in easily obtained oral fluid (Deutsch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%